Manipulation in the Indonesian Translation of The Secret Garden and the Translation Product Quality - Annisa Nur Atikah; Issy Yuliasri; Hendi Pratama (English Education Journal, 2024)
This study examines the manipulation of the text in Frances Hodgson Burnett's English novel "The Secret Garden," translated as "Taman Rahasia." This study aimed to determine whether the translator made specific manipulations during the translation, identify the types of manipulations present in the Indonesian translation, and evaluate the translation quality. The study belongs to qualitative research, which focuses on identifying text manipulations when translating to Indonesian. The analysis involved identifying text-internal manipulations, as arranged by Dukate (2007), which included alterations at the level of words, phrases, clauses, sentences, and paragraphs. The research's result found that three types of six text-internal manipulation were present in the Indonesian translation. The most frequent type of manipulation was conscious handling, with the translator frequently using the reduction/deletion technique proposed by Molina and Albir to modify the target text. It was observed that the translator mainly omitted unnecessary information from the source text due to cultural and linguistic considerations. Based on the findings, the quality of translation is good, which has been proved by the highest frequency for accuracy, readability, and acceptability in score 3. This study can also contribute to the implications for teachers and students in a classroom setting as they explore the translation of literary works for learning English, introduce the language culture in English and Indonesia, and realize what aspects may lead to manipulation in translating text.